Artikel Review : Regulasi Suplemen Kesehatan - Dewi Rahmawati; Widji Soeratri; Dewi Febiyanti; Maulina Apriani; Nabilla Navyani P.A; Nurul Islami Ningtiyas; Zahwa Natasya Novita P. (Inovasi Kesehatan Global, 2025)
Supplement is a product that contains additional nutrients to complement food, generally containing one or more nutrients, like vitamins, minerals, amino acids, fiber, and fatty acids, are usually prepared in the form of tablets, capsules, or liquids like syrup. Supplements can help improve nutrition, The purpose of this review is to analyze the effectiveness and safety of using health supplements in preventing and overcoming nutritional deficiencies and improving the quality of life of individuals in this analysis is based on a literature review from the online platform used, namely google scholar and semantic. The results of the journal review in this article show that supplements, such as mangosteen effervescent tablets, vitamin C, and stevia, have significant benefits for health, including improving immunity, managing diabetes, and supporting disease recovery. Education and socialization succeeded in improving people's understanding of the wise use of supplements, with age, knowledge, and socioeconomic conditions influencing consumption behavior.